2013
DOI: 10.1186/2195-3007-3-14
|View full text |Cite
|
Sign up to set email alerts
|

Negative impacts of gambling on Asian families and communities in New Zealand

Abstract: This paper outlines a project that investigated the impact of gambling and problem gambling on the health and wellbeing of Asian families and communities in New Zealand. This 2-year, multi-phase qualitative project included focus group discussions and individual face-to-face interviews with stakeholders and individuals who have experienced or been impacted by problem gambling across New Zealand's five major Asian ethnic subgroups of Chinese, Indian, Korean, Southeast Asian and Asian with Refugee background. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…31 The feedback from stakeholders reinforces views of youth on how intergenerational issues can be explored with appropriate sensitivity, safety and respect for all involved, including parents. 21 Although racism and racial discrimination were felt strongly by the youth participants in the parallel study 21 and have been previously reported to be significant factor influencing the wellbeing of young Asians in New Zealand, 33 it was not a significant finding in this study. Racism and discrimination are not new ideas, but the significance of their influence on the health and wellbeing of ethnic minority youth in New Zealand has received attention only relatively recently.…”
Section: Discussionmentioning
confidence: 50%
“…31 The feedback from stakeholders reinforces views of youth on how intergenerational issues can be explored with appropriate sensitivity, safety and respect for all involved, including parents. 21 Although racism and racial discrimination were felt strongly by the youth participants in the parallel study 21 and have been previously reported to be significant factor influencing the wellbeing of young Asians in New Zealand, 33 it was not a significant finding in this study. Racism and discrimination are not new ideas, but the significance of their influence on the health and wellbeing of ethnic minority youth in New Zealand has received attention only relatively recently.…”
Section: Discussionmentioning
confidence: 50%
“…Family members of problem gamblers also reported being less optimistic about their future, having lower self-esteem and having no explicit goals in life compared to the non-problem gambling family members surveyed. Another study (Sobrun-Maharaj, Rossen & Wong 2013 ) revealed that adverse effects resulting from problem gambling among the Asian families and communities in New Zealand included social disconnection, family conflict such as aggression and violence towards family members, financial insecurity, and physical and mental health problems such as anxiety, anger, depression and insomnia. Studies examining how family coping strategies relate to these gambling related family impacts in Chinese communities are, however, non-existent.…”
Section: Background and Rationalementioning
confidence: 99%
“…Given the effect cultural beliefs and values can have on gambling-related perceptions and gambling behaviour (see Ji et al 2015 ; Kim 2011 ; Ohtsuka 2013 ; Raylu and Oei 2004 ; Sobrun-Maharaj et al 2012 ; Subramaniam et al 2015 ; Tse et al 2012 ; Urale et al 2015 ), an accurate understanding of gambling harm among different ethnic communities requires an understanding of the cultural contexts in which gambling behaviour occurs and manifests harm. Some studies have identified that gambling harms experienced by Pacific people include negative effects on health, finances, employment and education; disruptions to household and extended family relationships; unfulfilled childcare; reduced community contributions; and unmet responsibilities being passed on to family members (Bellringer et al 2013 ; Guttenbeil-Po’uhila et al 2004 ; Lin et al 2011 ; Perese and Faleafa 2000 ).…”
Section: Introductionmentioning
confidence: 99%